Collaboration between two CF centers; one in USA and one in Turkey before and during CoV2 pandemic - GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA (My University, 2022)
To address the discrepancy in the quality of care and outcomes between cystic fibrosis centers (CFCs) in high-income countries and limited resources countries (LRCs), a collaboration between our team at the University of Michigan CFC (UMCFC) and a CF center in Turkey (Marmara University CFC [MUCFC], Istanbul) was established. The collaboration included evaluation of all aspects of care and initiation of quality improvement (QI) measures. Teaching and implementing QI tools has led to start of improvement in MUCFC care. Close monitoring and sharing resources like UMCFC algorithms, protocols, and QI processes were done.
Keywords: PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; BMI; cystic fibrosis; FEV1; high-income countries; infection prevention & control; low resources countries; quality improvement